2021
DOI: 10.24908/pceea.vi0.14888
|View full text |Cite
|
Sign up to set email alerts
|

Learning Electronics Through Storytelling

Abstract: STEM (Science, Technology, Engineering, and Math) initiatives have expanded to include ‘art’ withthe moniker: STEAM (Science, Technology, Engineering, Art, and Math). This acknowledges the importance of creativity in the technical fields and poses the question: How do we incorporate art into the engineering classroom? This paper presents one attempt to incorporate the artof storytelling in a first-year engineering design course in January 2021. It was found that compared with students who received a traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…To introduce students to breadboards and basic electronics concepts, a storybook was developed with a fictional narrative on the right-hand pages and a technical description on the left-hand pages. 37 Figure 3 shows a sample page from the book.…”
Section: Breadboardia Storybookmentioning
confidence: 99%
See 2 more Smart Citations
“…To introduce students to breadboards and basic electronics concepts, a storybook was developed with a fictional narrative on the right-hand pages and a technical description on the left-hand pages. 37 Figure 3 shows a sample page from the book.…”
Section: Breadboardia Storybookmentioning
confidence: 99%
“…It was found that students who use the storybook completed the activity significantly faster than students who received a lecture (P < 0.05). 37 The activity requires electronic components and copies of the storybook. Some set-up is required to load the Arduinos and prepare the kits.…”
Section: Breadboardia Storybookmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, two-way ANOVA was employed to compare time and knowledge variables controlling for participant experience and instruction method. These results were published in a conference paper and an expanded journal article [9,23]. The study was repeated the following year in a first-year engineering design course using the same protocol, with 31 students in each of the two sections.…”
Section: Methodsmentioning
confidence: 99%